Risk of the Cross-Sectional Returns in Foreign Exchange Markets - Yang, Jinsuk; Kang, Sung Myun; Heo, Sang Woo (Journal of Applied Business and Economics, 2022)
The cross-section of foreign exchange returns has substantial exposure to the risk captured by the marketwide moments. We investigate if the foreign exchange market risks are appropriately priced in exchange rates of individual countries. We use cross-sectional analysis to explore the correlation between the marketwide risks and risk premiums of foreign currencies. The results from analysis with the Fama and MacBeth regressions indicate that, while the market beta is negatively associated with the cross-sectional returns in foreign exchange markets, higher exposures to market-wide volatility, skewness, and kurtosis are positively related to individual countries’ exchange-rate risk premiums. These results are robust in the empirical setup.